2021
DOI: 10.2903/sp.efsa.2021.en-1995
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wild boar‐domestic pig interface in Europe: spatial overlapping and fine resolution approach in several countries

Abstract: The present document has been produced and adopted by the bodies identified above as authors. This task has been carried out exclusively by the authors in the context of a contract between the European Food Safety Authority and the authors, awarded following a tender procedure. The present document is published complying with the transparency principle to which the Authority is subject. It may not be considered as an output adopted by the Authority. The European Food Safety Authority reserves its rights, view … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This includes communication campaigns to promote awareness about ASF, targeting to pig owners and other stakeholders (such as hunters and the general public) as a preventive ASF control strategy, and direct formation of veterinarian on development of farm specific biosecurity plans against wildlife. ENETWILD also aims at defining the spatial interface between wild boar and domestic pigs in Europe (ENETWILD-Consortium et al 2021b) and described the different sources of data for domestic pigs at European scale as well as their potential to be used to define the interface with the wild boar. ENETWILD developed preliminary risk maps of possible spatial interaction between domestic pig farms (based on modelling at continental level) and wild boar (ENETWILD-Consortium et al 2021b).…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes communication campaigns to promote awareness about ASF, targeting to pig owners and other stakeholders (such as hunters and the general public) as a preventive ASF control strategy, and direct formation of veterinarian on development of farm specific biosecurity plans against wildlife. ENETWILD also aims at defining the spatial interface between wild boar and domestic pigs in Europe (ENETWILD-Consortium et al 2021b) and described the different sources of data for domestic pigs at European scale as well as their potential to be used to define the interface with the wild boar. ENETWILD developed preliminary risk maps of possible spatial interaction between domestic pig farms (based on modelling at continental level) and wild boar (ENETWILD-Consortium et al 2021b).…”
Section: Recommendationsmentioning
confidence: 99%
“…ENETWILD also aims at defining the spatial interface between wild boar and domestic pigs in Europe (ENETWILD-Consortium et al 2021b) and described the different sources of data for domestic pigs at European scale as well as their potential to be used to define the interface with the wild boar. ENETWILD developed preliminary risk maps of possible spatial interaction between domestic pig farms (based on modelling at continental level) and wild boar (ENETWILD-Consortium et al 2021b). Our preliminary prediction model of the interface between pig and wild boar in Europe indicated that the maximum risk interface (in term of spatial overlapping, without considering the type of production) is scattered over the area delimited by Germany, Poland, North Italy, and Serbia, so as in Northwest Spain.…”
Section: Recommendationsmentioning
confidence: 99%
“…This RO will allow the quantification of the overlap of WB and pigs therein on different production systems. To date, the interface has been spatially depicted in only a few countries, and considering the typology of pig farms, only in Romania (ENETWILD-consortium et al, 2021).…”
Section: Current Situation For the Particular Research Objective In T...mentioning
confidence: 99%